Initial periodontal treatment affects nucleotide-binding domain leucine-rich repeat-containing protein 3 inflammasome priming in peripheral blood mononuclear cells. (February 2020) - Higuchi, Kanako; SM, Ziauddin; Yamashita, Yasunori; Ozaki, Yukio; Yoshimura, Atsutoshi
Highlights: Expression of IL-1β and ASC in PBMCs decreased after initial periodontal treatment. PBMCs stimulated with silica crystals secreted IL-1β. IL-1β secretion by PBMCs decreased after treatment in low BOP percentages group. IL-1β secretion by PBMCs increased after treatment in high BOP percentages group. Abstract: Objective: Accumulating evidence suggests an association between periodontitis and several systemic diseases, such as atherosclerosis. In the lesions of these diseases, nucleotide-binding domain leucine-rich repeat-containing protein 3 (NLRP3), apoptosis-associated speck-like protein containing a caspase activation and recruitment domain (ASC) and caspase-1 form inflammasome complex, which leads to the functional maturation of interleukin (IL)-1β via cleavage of caspase-1 in macrophages. IL-1β plays a critical role in the etiology of these diseases; however, inflammasome priming—specifically, IL-1β and NLRP3 upregulation—is necessary for effective IL-1β production. We investigated the effect of initial periodontal treatment on the inflammasome priming of peripheral blood mononuclear cells (PBMCs). Methods: Twenty-two patients with chronic periodontitis were enrolled in this study and given initial periodontal treatment. Peripheral blood samples were collected at baseline and re-evaluation (41.1 ± 29.1 d after the treatment), and the relative expression of IL-1β, and three inflammasome components, ASC, NLRP3 and Caspase-1, mRNA was determined using quantitative reverse transcription PCR. PBMCs were stimulated with silica crystals, and the IL-1β secretion was measured via enzyme-linked immunosorbent assay. Results: Probing pocket depth and bleeding on probing (BOP) were significantly improved after the treatment. Expression of IL-1β and ASC in the PBMCs decreased after the treatment. PBMCs stimulated with silica crystals secreted IL-1β. The treatment attenuated IL-1β secretion by PBMCs in low BOP percentages group whereas IL-1β secretion was increased in high BOP percentages group. Conclusion: Periodontal treatment altered the inflammasome priming status of the PBMCs, however, the effects on systemic diseases need to be further investigated.